2021
DOI: 10.1371/journal.pone.0251795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salbutamol on the kinetics of sevoflurane and the occurrence of early postoperative pulmonary complications in patients with mild-to-moderate chronic obstructive pulmonary disease: A randomized controlled study

Abstract: Bronchodilators dilate the bronchi and increase lung volumes, thereby improving respiratory physiology in patients with chronic obstructive pulmonary disease (COPD). However, their effects on sevoflurane kinetics remain unknown. We aimed to determine whether inhaled salbutamol affected the wash-in and wash-out kinetics of sevoflurane and the occurrence of early postoperative pulmonary complications (PPCs) in patients with COPD undergoing elective surgery. This randomized, placebo-controlled study included 63 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…2023; 33(3):e130800. showed that preoperative β2 agonists (salbutamol) 30 min before surgery decreased the occurrence of bronchospasm and new-onset pulmonary infiltration in patients (22). Akcora et al used a combination of nebulized albuterol and budesonide starting right after the hospitalization and stated a significant decrease in bronchospasm and desaturation during bronchoscopies in their retrospective study (15).…”
mentioning
confidence: 99%
“…2023; 33(3):e130800. showed that preoperative β2 agonists (salbutamol) 30 min before surgery decreased the occurrence of bronchospasm and new-onset pulmonary infiltration in patients (22). Akcora et al used a combination of nebulized albuterol and budesonide starting right after the hospitalization and stated a significant decrease in bronchospasm and desaturation during bronchoscopies in their retrospective study (15).…”
mentioning
confidence: 99%